2019
DOI: 10.1186/s13011-019-0202-9
|View full text |Cite
|
Sign up to set email alerts
|

Help seeking behavior for problematic substance uses in north-West Ethiopia

Abstract: Background Substance miss use and neuro-psychiatric conditions are a growing public health challenges, but 76 to 85% of people with those disorders in low and middle-income countries did not receive treatment. The aim of this study was to see help seeking behavior and determinant factors in residents with problematic substance uses. Methods A total of 2400 participants had screened for problematic substance uses and 548 participants were found positive for problematic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
0
7
0
3
Order By: Relevance
“…If a participant score two or more positive answers from the total of four questions was considered positive for problematic substance use. The CAGE AID has been used in previous Ethiopian studies [18,19]. A 12 months suicidal behavior was assessed by using suicidal behavior questionnaire revised (SBQ-R).…”
Section: Measurementsmentioning
confidence: 99%
“…If a participant score two or more positive answers from the total of four questions was considered positive for problematic substance use. The CAGE AID has been used in previous Ethiopian studies [18,19]. A 12 months suicidal behavior was assessed by using suicidal behavior questionnaire revised (SBQ-R).…”
Section: Measurementsmentioning
confidence: 99%
“…Each item of questions was rated on a “yes” or “no” response which is valued at one point (1) and zero (0). CAGE-AID is an important tool to assess for other problematic drug uses (khat, tobacco, and cannabis) in addition to screening problematic alcohol uses in the community, and also has been utilized by previous Ethiopian studies [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“… 1 - 3 It is associated with significant problems, such as risky sexual behavior, substance use dependencies and disorders, mental problem and disability, failure to meet primary responsibilities at work, school, or home. 1 , 4 - 6 Substance use has also been a part of social life and integrated into the culture of many communities across the world for millennia. 7 , 8…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature shows that substances such as alcohol, khat, cigarette, and hashish are the most commonly used by students in Ethiopian universities. 1 , 4 , 16 , 27 , 29 , 30 These studies only identified the factors associated with any substance use without identifying or exploring the factors that contribute to the use of these individual substances. Thus, this study attempted to identify the associated risk factor for alcohol, khat, cigarette, and hashish use separately by comparing one with another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation